Correlated contemporary evolution of life history traits in New Zealand Chinook salmon, Oncorhynchus tshawytscha - Kinnison, M T (Nature Publishing Group, 2011)
Size at age and age at maturity are important life history traits, affecting individual fitness and population demography. In salmon and other organisms, size and growth rate are commonly considered cues for maturation and thus age at maturity may or may not evolve independently of these features. Recent concerns surrounding the potential phenotypic and demographic responses of populations facing anthropogenic disturbances, such as climate change and harvest, place a premium on understanding the evolutionary genetic basis for evolution in size at age and age at maturity. In this study, we present the findings from a set of common-garden rearing experiments that empirically assess the heritable basis of phenotypic divergence in size at age and age at maturity in Chinook salmon (Oncorhynchus tshawytscha) populations introduced to New Zealand. We found consistent evidence of heritable differences among populations in both size at age and age at maturity, often corresponding to patterns observed in the wild. Populations diverged in size and growth profiles, even when accounting for eventual age at maturation. By contrast, most, but not all, cases of divergence in age at maturity were driven by the differences in size or growth rate rather than differences in the threshold relationship linking growth rate and probability of maturation. These findings help us understand how life histories may evolve through trait interactions in populations exposed to natural and anthropogenic disturbances, and how we might best detect such evolution.